Applicability of modern information technology tools to materials cataloging and coproducing the central NUKAT catalog - Jóźwiak, Monika (Biblioteka Uniwersytecka we Wrocławiu, 2015)
The article presents the working tools used for shared cataloging in the Union Catalog of Polish Research Library Collections (NUKAT). It insights into the fundamentals of librarians' field of work while cataloging documents and points out that the tools developed rendered available by the NUKAT Centre employees are used by partner libraries. Tasks and projects worked on by the NUKAT Centre with cooperative cataloging libraries are also discussed. Described is also the dynamics of evolution of cataloging standards and principles as well as the direction of their further development.
Keywords: shared cataloging; RDA; VIAF; central catalog; NUKAT; ISNI